2021
DOI: 10.1093/ije/dyab203
|View full text |Cite
|
Sign up to set email alerts
|

Trans-ethnic Mendelian-randomization study reveals causal relationships between cardiometabolic factors and chronic kidney disease

Abstract: Background This study was to systematically test whether previously reported risk factors for chronic kidney disease (CKD) are causally related to CKD in European and East Asian ancestries using Mendelian randomization. Methods A total of 45 risk factors with genetic data in European ancestry and 17 risk factors in East Asian participants were identified as exposures from PubMed. We defined the CKD by clinical diagnosis or by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 94 publications
(96 reference statements)
5
38
2
Order By: Relevance
“…Nonetheless, tracking of body size is not likely to entirely explain the association as children with severe obesity already display kidney abnormalities [ 7 ]. Additionally, a large mendelian randomization study found evidence for a causal relationship between adult BMI levels of overweight or obesity with CKD [ 8 ], supporting that the associations in our study reflect an effect of BMI.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nonetheless, tracking of body size is not likely to entirely explain the association as children with severe obesity already display kidney abnormalities [ 7 ]. Additionally, a large mendelian randomization study found evidence for a causal relationship between adult BMI levels of overweight or obesity with CKD [ 8 ], supporting that the associations in our study reflect an effect of BMI.…”
Section: Discussionsupporting
confidence: 84%
“…The primary risk factors for CKD vary by country; however, diabetes and hypertension are among the established leading causes, particularly in high-income countries [2,4]. Additionally, increasing evidence supports that excess adult adiposity is a substantial and causal contributor to CKD risk [5][6][7][8]. Although overweight and obesity are closely related to both diabetes and hypertension, it is suggested that excess adiposity may have effects on CKD risks independent of these 2 major causes of CKD [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MR studies using these individuals could have been biased by population stratification or different ancestries (Davies et al, 2019). In fact, Zheng et al found that hypertension could play different causal roles on chronic kidney disease across ancestries (Zheng et al, 2022). Fourth, the underlying mechanisms about the causal association between educational attainment and IS remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Others have developed and applied trans-ancestry methods for genetic correlation 11 , polygenic risk score 12,13 and fine mapping 14,15 analyses. However, multi-ancestry causal inference using MR is still in its infancy 16 . One major issue restricting the development of multi-ancestry MR is the unbalanced representation of genome-wide association study (GWAS) samples across different ethnic groups, with one commentary reporting that across published GWAS, 78% of participants were of European ancestry 17 .…”
Section: Introductionmentioning
confidence: 99%